A General Equilibrium Model of Portfolio Insurance - Basak, Suleyman (Review of Financial Studies, 1995)
This article examines the effects of portfolio insurance on market and asset price dynamics in a general equilibrium continuous-time model. Portfolio insurers are modeled as expected utility maximizing agents. Martingale methods are employed in solving the individual agents' dynamic consumption-portfolio problems. Comparisons are made between the optimal consumption processes, optimally invested wealth and portfolio strategies of the portfolio insurers and "normal agents." At a general equilibrium level, comparisons across economies reveal that the market volatility and risk premium are decreased, and the asset and market price levels increased, by the presence of portfolio insurance. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.